Intravaginal testicular torsion in newborns. To fix or not to fix the contralateral testis? - G. Bordin; F. Parolini; A. Morandi; G. Farris; E.M. Leva; M. Torricelli (PAGEPress Publications, 2013)
Scrotal swelling suggesting testicular torsion is a rare urological emergency which requires a clinical urgent evaluation and most of the times must be managed surgically. In newborns it can occur in the postnatal period, usually within the twenty-eighth day of life, or more frequently in utero, during the descent of the testis into the scrotum. Usually its poor fixedness allows the testis an abnormal mobility inside the scrotum, configuring the framework of extravaginal torsion. On the contrary during the perinatal period a twist that takes place inside the tunica vaginalis, known as intravaginal torsion, is extremely uncommon and only few cases are well documented in the literature. Authors present a rare case of intravaginal testicular torsion occurred in perinatal period. In this situation only the early surgical exploration of the scrotum may allow the rescue of the gonad, although in rare cases. Timing of surgical treatment and need for contralateral testicular fixation remain controversial. However since the anatomical defect of the tunica vaginalis can be bilateral the surgical fixation even of the contralateral testis is important, now or later, in order to prevent any future torsion of this gonad. The authors also present a brief review of recent literature on the subject.